Development of Physics Learning Based on Video Integrated Flipped Classroom Model Using Moodle - Silfi sutri Insani; Pakhrur Razi (PILLAR OF PHYSICS EDUCATION, 2023)
21st century education requires students to have skills that can answer the challenges of revolution 4.0. Skills that should be mastered are data, technology and human literacy. However, the government's efforts to issue policies to implement scientific literacy of the 2013 Curriculum to boost Indonesian education have not been optimized by schools. This is known by the lack of technology adoption in learning tools by educators. In order for students to have skills in the era of revolution 4.0, a learning resource was developed in the form of physics learning based on video integrated Flipped Classroom using Moodle. The purpose of this study is determine the validity and practicality of physics learning videos. This research was conducted using the Research and Development (R&D) model and quantitative descriptive methodology. This research using validity and practicality instrument test for analyze data to know satisfied product learning. Product validation was carried out by expert and received a score of 88 with a very valid category. After making revisions according to expert advice, practicality test was carried out at SMAN 1 Pariaman. Practicality was carried out by physics teachers and students in limit scale. Practicality results were obtained with a score of 86 from teacher responses and a score of 87 from participant responses. From the results of validity and practicality, the physics learning based on video integrated flipped classroom model using Moodle is categorized as very valid and very satisfied  so it is feasible to use in the learning process in the classroom.